A case study of a body weight control programme for elite Chinese female Gymnasts in preparation for the 2008 Olympic Games - Chen, H.; Wang, M.; Liu, S.; Lu, S.; Zhang, P.; Zhou, W.; Sun, W. (Science of Gymnastics Journal, 2009)
For top level female gymnasts , effective body fat reduction is a long-term process, often resulting in various issues; how to keep the physical fitness at an optimal level? How to control the amount of training to improve skill and performance? This report presents a case study of a successful weightloss program used by the Chinese National Gymnastics Team when preparing for the 2008 Olympic Games.